A coordenaç\~ao de programas prioritários sob a perspectiva do núcleo do governo federal (2007-2014) - Pedro Cavalcante; Alexandre de Ávila Gomide; Sheila Barbosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The paper's main goal is to advance in the knowledge of a key function of the government: the policy coordination. This is even more relevant within the core of the government, which is a set of institutions and actors that provide direct support to implementation of priority actions defined by the president. Thus, the research analyzes what mechanisms, instruments and levels of coordination are actually used in the policymaking of four strategic policies during the Lula's and Dilma's administration, namely: i) Programa Bolsa Família (PBF); ii) Programa de Aceleraç\~ao do Crescimento (PAC); iii) Programa Brasil Sem Miséria (BSM); e iv) Programa de Investimento em Logística (PIL). The investigation employed bibliographic review, content analysis of official publications and, mainly, interviews with actors who occupied key positions in the Presidency and Ministries of Finance and Planning in both administrations. The main conclusion is that in spite of the existence of various formal and procedural coordination instruments, in practice, the instruments most used in priority policies coordination are the ones informal and designed ad hoc for such programs. In addition, the hierarchical mechanism shares space with intra-governmental networking strategies, especially to solve conflicts and disagreements among ministries.
Keywords: H83; 330; governmental coordination; public policy; core of government; Executive branch; Brazil